Preoperative Anxiety in Patients With Myasthenia Gravis and Risk for Myasthenic Crisis After Extended Transsternal Thymectomy: A CONSORT Study. Issue 10 (March 2016) - Zou, Jianyong; Su, Chunhua; Lun, Xueping; Liu, Weibing; Yang, Weiling; Zhong, Beilong; Zhu, Haoshuai; Lei, Yiyan; Luo, Honghe; Chen, Zhenguang
Abstract : Abstract: A thymectomy can ameliorate the symptoms of myasthenia gravis (MG) and prevent the progression of ocular MG (OMG) to generalized MG (GMG). However, postoperative myasthenic crisis (POMC) is a serious post-thymectomy complication. Preoperative anxiety (POA) is common but typically neglected in MG patients. The association of POA with POMC has not yet been examined. From June 2007 to December 2013, 541 cases of MG were admitted to the First Affiliated Hospital of Sun Yat-sen University (Guangzhou, China). All cases underwent extended transsternal thymectomy (ETT). The clinical and pathological characteristics of these patients, including POA and POMC, were analyzed. A total of 179 patients experienced POA and 67 patients experienced POMC. Patients with POA were more likely to have POMC, a thymoma, and an ectopic thymus. Univariate analysis showed that POMC correlated with POA, presence of an ectopic thymus, dose of pyridostigmine bromide (PYR), presence of a thymoma, MGFA stage, preoperative myasthenic crisis, and postoperative pneumonia. Multivariate logistic regression analysis showed that the independent risk factors for POMC were POA, preoperative myasthenic crisis, higher dose of PYR, and postoperative pneumonia. Our results suggest that clinicians should consider the risk factors for POMC—especially preoperative anxiety—before performing a thymectomy in patients with MG.